Pengaruh Kombinasi Nilai EC (Electrical Conductivity) dan Tekanan Aerasi Terhadap Pertumbuhan dan Hasil Setek Batang Tanaman Mint (Mentha spicata L.) Pada Hidroponik Sistem Rakit Apung - Namira Siti Hajar; Darso Sugiono; Rommy Andika Laksono (Jurnal Ilmiah Wahana Pendidikan, 2022)
Public interest in hydroponic mint is increasing in the market because mint is one of the herbal plants used as anti-bacterial and antiviral drugs (Riyanti, 2020). However, there are obstacles in cultivating mint plants, namely the small number of seeds and the availability of seeds so that the stem cutting method was chosen to increase mint production. In addition, mint cultivation uses a floating raft hydroponic system that can provide good plant nutrition and easy maintenance. This study aims to obtain the right combination of EC values ​​and aeration pressure for the growth and yield of mint plant stem cuttings. The research was conducted at the Telaga Desa screen house located in the KIIC Industrial area, Jl. Permata Raya, Puseurjaya, Kec. Telukjambe Timur, Karawang Regency from May to June 2022. The research method used was an experimental method with a single factor Randomized Block Design (RBD) environment consisting of 10 treatments with 3 replications. The data were analyzed by analysis of variance and if the 5% level F test showed significantly different results, then continued with the DMRT (Duncan Multiple Range Test) test at the 5% level. Parameters observed included number of leaves (strands), root length (cm), plant height (cm), plant fresh weight (grams), and plant growth rate (cm/week). The results showed that there was a significantly different effect of the combination of EC value and aeration pressure on the number of leaves aged 6 WAP, root length 6 WAP and the yield of fresh weight of the plant. The C4 treatment, which was a combination of EC 3.0 mS/cm + Aerator 0.012 mPa, gave the highest yield on the average number of plant leaves, which was 243 leaves, the average plant root length was 91.82 cm and the yield of fresh weight of the plant was 64.91 grams.